Exploration and Practice of Annual Safety Report Regulation for Long-Distance Water Diversion Projects - HU Jiang; MA Fuheng; SHENG Jinbao; DAI Zhanqiang; LI Shuncai; FU Youqun (Renmin Zhujiang)
Long-distance water diversion projects are important strategic infrastructure to optimize the patterns of water resource allocation,which are characterized by long distances,many hydraulic structures,complex geological and environmental conditions,and high maintenance requirements.The long-term safe operation of these projects has been highly concerned.The annual safety report of these projects is an effective means to grasp the engineering status in a timely and dynamic manner.On the basis of the characteristics of these projects and the discussion on the existing basis and compilation principles of annual safety reports,the organization and implementation of the main work in annual reports,such as safety inspection,safety detection,and safety assessment,are explored,and the regulation of an annual safety report is proposed.According to the practice of the first annual safety report on the central route of the South-to-North Water Diversion Project,the key contents of the annual safety report,including safety inspection,safety detection,and safety monitoring,as well as operational management contents such as dispatching operation,maintenance,safety production,and emergency management are briefly introduced.Finally,the experience,understanding,and difficulty of annual safety report compilation are summarized.The successful application of the annual safety report in the central route project can provide a reference for similar projects.